Nursing team's adoption the surgical checklist: a narrative review (Research, Society and Development, 2021)
Safe surgery involves practices adopted to reduce the risks of adverse events and damage that may occur in the patient before, during or after surgery. The introduction of the safe surgical checklist, also known as checklist, is a step towards a new safety culture in the operating room. This study aims to investigate the production of knowledge about the access to the checklist of safe surgery. This is a bibliographic review study on the access to the use of the checklist in the operating room. The nursing team plays an essential role in adhering to the safe surgery checklist, as it is responsible for qualification, communication and professional training, with a view to improving the service and reducing adverse events. Checklist adhering should be improved to contribute to the reduction of adverse events and the promotion of patient safety. The study pointed out that there are several publications that demonstrate the real effectiveness of the checklist in the literature, but it was evidenced that its suitability in clinical practice is still low, pointing out a gap in the knowledge to be filled by nursing, especially the teams working in the operating room.